Cell Phone Information Seeking Explains Blood Pressure in African American Women. (May 2018) - Jones, Lenette M.; Veinot, Tiffany C.; Pressler, Susan J.
Although cell phone use and Internet access via cell phone is not marked by racial disparities, little is known about how cell phone use relates to blood pressure and health information seeking behaviors. The purposes of this study were to (a) describe Internet activities, cell phone use, and information seeking; (b) determine differences in blood pressure and information seeking between cell phone information seekers and nonseekers; and (c) examine cell phone information seeking as a predictor of blood pressure in African American women. Participants ( N = 147) completed a survey and had their blood pressure measured. Independent-sample t tests showed a significant difference in systolic blood pressure in cell phone information seekers and nonseekers. Linear regression revealed cell phone information seeking as an independent predictor of systolic blood pressure, despite confounders. It is possible that cell phone information seekers were using health information to make decisions about self-management of blood pressure.